Analisis pengaruh inflasi, pendidikan dan pertumbuhan ekonomi terhadap tingkat pengangguran terbuka dan kemiskinan di Provinsi Jambi - Muhammad Azis; Yulmardi Yulmardi; Nurhayani Nurhayani (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2021)
The purposes of this study are 1) To determine and analyze the development of inflation, education, economic growth, open unemployment, and poverty in Jambi Province; and 2) To determine and analyze the effect of inflation, education, and economic growth, on the open unemployment rate and poverty in Jambi Province. The data used in this research is secondary data. The model used in this study is a multiple linear regression model. The results show that the average development of inflation is 11.35%, education is 1.25%, economic growth is -2.64%, TPT is 1.99%, and poverty is -2.74%. Furthermore, the analysis results show that directly inflation and economic growth have a significant effect on TPT in Jambi Province (P<0.05). At the same time, indirectly, only education variables affect poverty in Jambi Province (P<0.05). Keywords: Inflation, Education, Economic growth, Open unemployment, Poverty